2022
DOI: 10.1186/s12882-022-02708-8
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury following major emergency abdominal surgery – a retrospective cohort study based on medical records data

Abstract: Background Acute Kidney Injury (AKI) is a frequent and serious postoperative complication in trauma or critically ill patients in the intensive care unit. We aimed to estimate the risk of AKI following major emergency abdominal surgery and the association between AKI and 90-day postoperative mortality. Methods In this retrospective cohort study, we included patients undergoing major emergency abdominal surgery at the Department of Surgery, Zealand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…To identify predictive factors for postoperative AKI, patients were classified into two groups based on whether postoperative AKI occurred. The risk factors for postoperative AKI were examined by univariate and multivariate logistic regression analyses which included the following variables: old age (> 65 years); sex (male); higher ASA status (3,4,5); (14) obesity (body mass index [BMI] > 25 kg•m -2 ) (9, 10); medical history of hypertension, diabetes mellitus, heart disease, liver disease, neurovascular disease, or renal disease; moderate or severe anemia (hemoglobin < 11 g•dL -1 ) (18); low serum albumin (< 3.5 g•dL -1 ); anesthetic type (total intravenous anesthesia); duration of surgery (> 3 hours); transfusion (positive); liberal (> 12 mL•kg -1 •hr -1 ) or restrictive (< 4 mL•kg -1 •hr -1 ) fluid administration (19,20); emergent operation, low PPI; and hypotension (21). Multivariate logistic regression was used to calculate ORs and 95% confidence intervals (CIs) after simultaneously controlling for potential confounders.…”
Section: Variables and Statistical Analysismentioning
confidence: 99%
“…To identify predictive factors for postoperative AKI, patients were classified into two groups based on whether postoperative AKI occurred. The risk factors for postoperative AKI were examined by univariate and multivariate logistic regression analyses which included the following variables: old age (> 65 years); sex (male); higher ASA status (3,4,5); (14) obesity (body mass index [BMI] > 25 kg•m -2 ) (9, 10); medical history of hypertension, diabetes mellitus, heart disease, liver disease, neurovascular disease, or renal disease; moderate or severe anemia (hemoglobin < 11 g•dL -1 ) (18); low serum albumin (< 3.5 g•dL -1 ); anesthetic type (total intravenous anesthesia); duration of surgery (> 3 hours); transfusion (positive); liberal (> 12 mL•kg -1 •hr -1 ) or restrictive (< 4 mL•kg -1 •hr -1 ) fluid administration (19,20); emergent operation, low PPI; and hypotension (21). Multivariate logistic regression was used to calculate ORs and 95% confidence intervals (CIs) after simultaneously controlling for potential confounders.…”
Section: Variables and Statistical Analysismentioning
confidence: 99%
“…To our knowledge, there was only one previous study reporting the risk factor of AKI after emergency abdominal surgery. 9 Hypertension and intraoperative peritoneal contamination were reported as independent risk factors of AKI.…”
Section: Discussionmentioning
confidence: 99%
“…Patients undergoing emergency abdominal surgery show a septic condition in about 40% at the time of surgery, and elderly patients have particularly poorly controlled comorbidities 5,9 . These patients also frequently present with deranged body homeostasis, signi cant physiologic insult, stress response and gastrointestinal dysfunction 10 .…”
Section: Introductionmentioning
confidence: 99%
“…A prospective study including 800 women that underwent hysterectomy revealed that visual inspection detected 38% of bladder injuries, whereas only 7% of ureteral injuries were diagnosed 13 . Meanwhile, randomized controlled studies have demonstrated that the use of prophylactic stents in gynecological procedures has yielded inconsistent results when it comes to reducing the likelihood of ureteral injury 11,24,25 . It may, however, minimize the diagnostic delay and potentially decrease postoperative morbidity 26 .…”
Section: Intraoperative Diagnostic Methods For the Detection Of Urina...mentioning
confidence: 99%